"We can't save the planet, we're too busy saving lives": Exploring beliefs about decarbonizing the NHS - F Fylan; G Allison (Elsevier, 2023)
Background: If health and social care delivery systems are to achieve net zero targets, fundamental changes are required to how organizations deliver care, how individuals practice clinically, how people access care, and how systems reduce the demand for healthcare. This paper explores how professionals, patients and citizens respond to this need for change. Methods: We conducted a mixed methods study, comprising 12 deliberative workshops (n = 35) and a survey (n = 413) with health and social care staff, patients and citizens in the North of England. Results: We found that while few people were aware of the net zero target, they supported it. Some, however, questioned organizational commitment, highlighting potential conflicts between cost and sustainability. Staff described a lack of agency to make changes to their practice, despite identifying many opportunities to do so. Some believed that healthcare should be exempt from carbon reduction targets. The strongest messages we found to interest, empower, and motivate people to make changes are: that individual actions matter; that we have a responsibility to set a good example of tackling climate change; and that making changes saves lives and should be a priority. We also found that people need to be reassured that the changes will not adversely affect clinical outcomes. Finally, progress towards targets needs to be tracked and publicly available. Conclusion: Our results indicate a need for clear leadership which gives sustainability a higher priority, a need for staff training to enable conversations about the environmental effects of treatment, and support for shifting the focus from treating illness to promoting health.